Integrated Photo‐Responsive Batteries for Solar Energy Harnessing: Recent Advances, Challenges, and Opportunities. Issue 4 (16th January 2020) - Fang, Zhengsong; Hu, Xuanhe; Yu, Dingshan
Abstract: Photo‐responsive batteries that enable the effective combination of solar harvesting and energy conversion/storage functionalities render a potential solution to achieve the large‐scale utilization of unlimited and cost‐effective solar energy and alleviate the limits of conventional energy storage devices. The internal integration of photo‐responsive electrodes into rechargeable batteries with the simplest two‐electrode configuration is regarded as a reliable and appealing strategy for highly‐efficient and low‐cost utilization of solar energy by simplifying the device architecture and improving the energy efficiency. This progress report provides a brief review on photo‐responsive batteries with integrated two‐electrode configuration that can achieve solar energy conversion/storage in one single device. The basic device architecture, operating principles and practical performance of various photo‐responsive systems based on solar energy harvesting in various batteries including Li ion batteries, Li−S batteries, Li−I batteries, dual‐liquid redox batteries, Li−O2 batteries, non‐Li anode‐O2 /air batteries are summarized and discussed. Finally, the future opportunities and challenges regarding the two‐electrode photo‐responsive batteries are proposed. Abstract : Illuminating battery design : The graphic shows an integrated photo‐responsive battery with the simplest two‐electrode configuration. This Minireview summarizes the recent advances of various photo‐responsive systems based on solar‐energy capture in various systems including Li ion, Li−S, Li−I, dual‐liquid redox, Li−O2, and non‐Li anode‐O2 /air batteries and highlights the future challenges and opportunities for the field.